Leading educational improvement in Trinidad and Tobago - James, Freddy (Taylor and Francis Online, 2010)
This Trinidad and Tobago (TandT) is currently undergoing major educational reforms and improvement at all levels of the system. Schools have been given responsibility for implementing changes through the establishment of school-based management. is your abstract School leaders now have the important role of initiating and implementing school improvement, which necessitate new forms of leadership. This raises the question of the leadership capacity and competencies that are required for school leaders to fulfill this role. This article focuses on educational improvement in TandT and its implications for school leadership. The study presented in this article utilized a qualitative interpretive research design employing a range of data collection methods, including questionnaires and interviews. The results of the study confirm a need for developing a new type of school leader who is: better trained, more research oriented; more of a risk taker and more autonomous.
Keywords: Educational improvement; Leadership; Trinidad and Tobago